Comparative Genomic and Transcriptomic Analysis Provides New Insights into the Aflatoxin B1 Biodegradability by Kocuria rosea from Deep Sea - Jingying Wang; Jun Nan (Microorganisms)
As a mycotoxin, aflatoxin B1 (AFB1) has attracted increasing attention due to its highly toxic effects, such as teratogen, carcinogen, and mutagen. AFB1-producing fungi have been found in both terrestrial and marine sources. Over the last two years, the marine-derived bacteria Kocuria rosea has shown the ability to degrade AFB1. However, no studies have yet explored the aflatoxin degradation potential in the genus Kocuria, and the molecular basis of aflatoxin metabolisms by strain has not yet been investigated. In this study, we first compared and analyzed the genomic features of 13 bacteria of the genus Kocuria by comparative genomic analysis and investigated the evolutionary patterns (evolutionary selection pressure analysis and gene family expansion analysis) and pan and core genomes of Kocuria strains. It was found that Kocuria genus strains showed high potential in the bioremediation of aromatic compounds and aflatoxin degradation. In addition, this study revealed 1421 differentially expressed genes and 752 upregulated genes between the aflatoxin group and the control group through transcriptome analysis and conducted functional annotation and analysis of functional enrichment. According to the expression and functional analysis of upregulated genes, the enzymes and genes (cytochrome P450, oxidoreductase, intradiol ring-cleavage dioxygenase, hydrolase, and monooxygenase) involved in the aflatoxin degradation of Kocuria rosea were screened. These findings indicate the potential of Kocuria rosea in the remediation of aflatoxin contamination and provide a foundation and direction for the further excavation of novel degradation genes, exploration of degradation mechanisms, and genomic modification.